2015
DOI: 10.1007/s00701-015-2383-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of unstable thoracolumbar burst fractures using pedicle instrumentation with and without fracture-level screws

Abstract: Short-segment stabilization in thoracolumbar burst fractures with additional screws at the level of the fracture results in an improved kyphosis correction, sagittal index, and compression ratio of the anterior vertebral height. However, long-term follow-up is needed to determine the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
3
44
1
Order By: Relevance
“…They found that a screw at the fracture level resulted in a greater fracture reduction but they did not report long term results. 15 These results are different than the data of this study. Both Waqar and Sapkas report higher incidence of metal work failure compared to this series.…”
Section: Review Of the Literaturecontrasting
confidence: 92%
See 1 more Smart Citation
“…They found that a screw at the fracture level resulted in a greater fracture reduction but they did not report long term results. 15 These results are different than the data of this study. Both Waqar and Sapkas report higher incidence of metal work failure compared to this series.…”
Section: Review Of the Literaturecontrasting
confidence: 92%
“…Posterior spinal instrumentation is the most frequent method of fixation due to the low morbidity and comorbidity. 15 Our results show that overall posterior fixation results in loss of correction over time. When there is no anterior support the injured intervertebral disc and the fractured vertebrae may collapse further and result in loss of the reduction by 7° to 9°.…”
Section: Review Of the Literaturementioning
confidence: 59%
“…Recent literature has shown that the six-screw short-segment construct can effectively prevent early implantation, especially in those with LCS ≤7, and can provide satisfactory clinical results for thoracolumbar burst fractures [23,24]. Compared to traditional four-screw short-segment fixation, short-segment fixation with screws placed at the fractured level can achieve better correction with a lower rate of implant failure [7,8]. Lin et al and Liao et al also demonstrated that a six-screw shortsegment construct had a lower implant failure rate with better alignment maintenance compared to transpedicular grafting with short-segment instrumentation [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the disadvantages of long-segment posterior fixation are a long surgical time, high amounts of blood loss, and the sacrifice of two or more motion segments. More recently, six-screw short-segment posterior fixation, which involves the placement of two pedicle screws at the fractured vertebrae, has gained increasing attention because this method can reduce the surgical time and hospital costs, preserve motion segments compared to long-segment posterior fixation, and provide greater mechanical strength to prevent early implant failure compared with traditional four-screw short-segment posterior fixation [6][7][8][9]. In addition, some authors have advised that four-screw shortsegment instrumentation should be augmented by bone cement or bone substitute at the fractured vertebrae for maintaining alignment and preventing implant failure [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, more postoperative morbidities are accompanied with the anterior approach as compared with the posterior approach [7][8][9]. In addition, spine surgeons are more familiar with posterior approach due to its easier application [10].…”
Section: Introductionmentioning
confidence: 99%